Synchronous occurrence of Waldenström macroglobulinemia and HER2-positive gastric adenocarcinoma with gastrointestinal stromal tumor: a rare case report - Jin, Yingming; Shi, Zhilong; Li, Kesang; Liu, Tianjiao; Fang, Zhi (Frontiers in Oncology, 2025)
There are very few reports of gastric cancer (GC) and gastrointestinal stromal tumor (GIST) occurring at the same time in the literature. In particular, the collision of GIST and human epidermal growth factor receptor-2 (HER-2)-positive gastric carcinoma in a patient with Waldenström macroglobulinemia (WM) has never been reported. We report the case of an 80-year-old male who initially presented with dizziness with fatigue for more than 1 month. He underwent total gastrectomy. Pathology revealed GC (moderately to poorly differentiated tubular adenocarcinoma), GIST (low-risk category) and low-grade small B-cell lymphoma with plasmacytoid differentiation. Furthermore, the diagnosis of WM was made after cytomorphologic and immunohistochemical analysis of the patient’s bone marrow revealed the presence of lymphoplasma cells along with the MYD88 L265P mutation and an increased level of serum monoclonal immunoglobulin M (IgM). To our knowledge, this is the first case of such an association where WM occurred with concomitant HER2-positive gastric adenocarcinoma and gastric GIST. A review of the literature concerning the incredibly uncommon simultaneous triple incidence of malignant tumors with distinct histogenesis is presented below.